2019
DOI: 10.3390/su11040965
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Cultural Leadership Styles for Social Entrepreneurship: A Theoretical Framework

Abstract: The purpose of this conceptual article is to understand how the interplay of national-level institutions of culturally endorsed leadership styles, government effectiveness, and societal trust affects individual likelihood to become social entrepreneurs. We present an institutional framework comprising cultural leadership styles (normative institutions), government effectiveness (regulatory institutions), and societal trust (cognitive institutions) to predict individual likelihood of social entrepreneurship. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 142 publications
(226 reference statements)
0
11
0
Order By: Relevance
“…Extant research has suggested that informal institutions may also influence sustainable development of societies. Informal institutions such as sustainability values [79] and culturally endorsed leadership theories [80] have been found to influence sustainable development activities in societies. In terms of future research, longitudinal studies can therefore examine the impact of the B&R initiative on the informal institutions of the host country.…”
Section: Discussionmentioning
confidence: 99%
“…Extant research has suggested that informal institutions may also influence sustainable development of societies. Informal institutions such as sustainability values [79] and culturally endorsed leadership theories [80] have been found to influence sustainable development activities in societies. In terms of future research, longitudinal studies can therefore examine the impact of the B&R initiative on the informal institutions of the host country.…”
Section: Discussionmentioning
confidence: 99%
“…Given that cultures shape EI, and EI shapes entrepreneurial behaviors, therefore by extension, the understanding of culture-specific EI has an important place in the culture-entrepreneurship fit perspective. EI is also known to shape pro-social behaviors (Côté, 2011), such that our proposed perspective can also inform theory on cross-cultural comparative social entrepreneurship (Muralidharan & Pathak, 2018, 2019). Further, a recent study has found that the effects of culture on behavioral dispositions are distal—mediated by cultural leadership styles (e.g., Stephan & Pathak, 2016)—rendering cultural leadership styles as more proximal influencers of entrepreneurial behaviors.…”
Section: Implications Of Culture-specific Emotional Intelligence For mentioning
confidence: 93%
“…Educational leadership (Sellami et al, 2019) is represented in school leadership (Bush & Glover, 2002;Bush & Heystek, 2006) through various forms. These include transformational leadership (Allix, 2000;Leithwood & Jantzi, 2006;Leithwood & Sleegers, 2006), instructional leadership (Feye, 2019;Hallinger, 2003;Southworth, 2002), constructive leadership (Kuhnert & Lewis, 1997), cultural leadership (Hallinger, 2004;Muralidharan & Pathak, 2019), teacher leadership (Berry, 2014;Harrison & Birky, 2011;Howe & Stubbs, 2001;Smylie & Denny, 1990), and change leadership (Wagner, 2018). It also includes learning leadership (Reeves, 2006), learningcentered leadership (Goldring at al., 2007), shared leadership (Lambert, 2002;Pearce & Conger, 2003;Pearce & Sims, 2000;Pearce et al, 2007), distributed leadership (Bolden, 2011;Harris, 2004;Spillane et al, 2004;Timperley, 2005), democratic leadership (Woods, 2004), situational leadership (Thompson & Glasø, 2015), system leadership (Ramosaj & Berisha, 2014), and collaborative leadership (Hallinger & Heck, 2010).…”
Section: The Concept Of School Leadershipmentioning
confidence: 99%
“…Principals' smart school leadership competencies are made up of several component competencies relating to different fundamental operational aspects of the school. These are teaching and learning instructional, cultural, strategic, educational managerial, and organizational managerial leadership competencies (Alvy & Robbins, 2005;Berlin et al, 1988;E-Lead, 2008;Fink & Resnick, 2001;Muralidharan & Pathak, 2019;Piaw et al, 2014;Robbins & Alvy, 2004).…”
Section: Smart School Leadership Competencymentioning
confidence: 99%
See 1 more Smart Citation